Measuring and improving the timeliness of vancomycin therapeutic drug monitoring and potential patient safety impacts - Belinda Chappell; Benita Suckling; Champika Pattullo (Elsevier, 2024)
Background: Timely vancomycin therapeutic drug monitoring (TDM) enables prompt dose adjustments and safe treatment. Local incidents prompted an investigation into the reasons for prolonged reporting times. Objectives: To investigate the variation in reporting times of vancomycin concentrations between hospitals with and without on-site TDM processing, and patient safety implications. Methods: Vancomycin concentration results for Hospital 1 (off-site monitoring), Hospitals 2 and 3 (both on-site monitoring) from June to December 2021 were retrospectively analysed. Retrospective data collection was repeated for Hospital 1 three months post on-site TDM commencement for comparison. Vancomycin clinical incidents at Hospital 1 were reviewed to identify examples of when delays in reporting of results potentially contributed towards adverse patient outcomes. Results: Hospital 1 had a median reporting time of 11.13 h compared with Hospital 2 and Hospital T3 (1.73 h and 1.70 h respectively). Following the commencement of on-site TDM at Hospital 1, the reporting time reduced to 1.33 h (p < 0.001). Several incidents at Hospital 1 during the period of off-site monitoring involved delays to TDM results. Conclusions: Off-site processing of TDM introduced significant delays in reporting of vancomycin concentrations, which was significantly improved by transitioning to onsite availability of testing. This study also highlights the impact of accurate problem identification in improving patient safety.